Effects of acute exposure to low-dose radiation on the characteristics of human bone marrow mesenchymal stromal/stem cells - Aya Fujishiro; Yasuo Miura; Masaki Iwasa; Sumie Fujii; Noriko Sugino; Akira Andoh; Hideyo Hirai; Taira Maekawa; Tatsuo Ichinohe (BMC, 2017)
Abstract Background In recent years, increasing attention has been paid to the effects of low-dose irradiation on human health. We examined whether low-dose irradiation affected the functions of mesenchymal stromal/stem cells (MSCs), which are tissue/organ-supportive stem cells, derived from bone marrow (BM). Methods Normal human BM-MSCs from five healthy individuals were used in this study. Culture-expanded BM-MSCs were exposed to 0.1 gray (Gy) of γ-radiation (Cesium-137) at a rate of 0.8 Gy/min (Ir-MSCs), and their expansion, multi-differentiation, and hematopoiesis-supportive capabilities were investigated. Results The expansion of BM-MSCs was transiently delayed after low-dose γ-irradiation compared with that of non-irradiated BM-MSCs (non-Ir-MSCs) in two out of five lots. Adipogenic and osteogenic differentiation capabilities were not significantly affected by low-dose irradiation, although one lot of BM-MSCs tended to have transiently reduced differentiation. When human BM hematopoietic stem/progenitor cells (HPCs) were co-cultured with Ir-MSCs, the generation of CD34+CD38+ cells from HPCs was enhanced compared with that in co-cultures with non-Ir-MSCs in two out of five lots. The mRNA expression level of interleukin (IL)-6 was increased and those of stem cell factor (SCF) and fms-related tyrosine kinase 3 ligand (Flt3L) were decreased in the affected lots of Ir-MSCs. In the other three lots of BM-MSCs, a cell growth delay, enhanced generation of CD34+CD38+ cells from HPCs in co-culture, and a combination of increased expression of IL-6 and decreased expression of SCF and Flt3L were not observed. Of note, the characteristics of these affected Ir-MSCs recovered to a similar level as those of non-Ir-MSCs following culture for 3 weeks. Conclusions Our results suggest that acute exposure to low-dose (0.1 Gy) radiation can transiently affect the functional characteristics of human BM-MSCs.